Cross border cooperation in low population density regions - Jan Mønnesland (European Regional Science Association (ERSA), 1998)
The paper is based on the ongoing intermediate evaluations of the three Interreg II A programmes between Sweden and Norway. Two of the three programmes cover extended geographic areas with a low population size. This means that the areas are very sparsely populated with European standards. A circumstance connected with this is that the immediate border region is almost uninhabited. The population centres are in many cases situated quite far from the border, which means that there are great distances between them. The paper intends to focus on the challenges for the evaluation due to these special circumstances of the Interreg II A programmes. The geographic extension, the low population density and the considerable distances between the population centres, distinguish the two northernmost of the programmes from the rest of Europe. This means that the Nordic programmes must adapt methods of implementing the general aims to these special conditions. In these areas, the distinction between <real< cross-border cooperation and regional development programmes on each side of the border is not so easy to withhold, as it is in continental Europe. One could argue that the low population density in these peripheral areas makes regional development programmes a prerequisite for any cross-border cooperation. Even if the Swedish and Norwegian regions are adjacent to each other, the distances between the regional centres implies that they cannot solely trust upon a traditional cross-border strategy for the co-operation. On the other hand, the fact that the regions are neighbours, implies that they should not use the same kind of long-distance network strategies as e.g. the Interreg II C programmes. A key issue in the paper is whether the actors in the Interreg II A programmes seems to be able to develop such a strategy or if they <just< a) land up in development programmes on each side of the border; or b) establishes <traditional< cross-border projects along the very sparsely populated immediate border area; or c) land up with a few specialised networks between the population centres.
Keywords: 330